Pharmacokinetics simulation of Metformin in type 2 Diabetes Mellitus. (February 2019) - Kartono, A; Malik, S; Syafutra, H; Wahyudi, ST; Sumaryada, T
Abstract: The aim of this study was to explore the pharmacokinetic relationship of metformin on glucose levels after the administration of metformin in type 2 diabetes mellitus. The pharmacokinetics of metformin was assessed using intravenous glucose tolerance tests before and after metformin administration. Type 2 diabetes mellitus is a metabolic disturbance which is caused by the pancreas that cannot produce enough insulin or body cannot use insulin which is produced effectively (low insulin sensitivity). Therefore, there is glucose level concentration escalation inside blood, where blood glucose level is more than normal level or known as hyperglycemia. Type 2 diabetes mellitus signed by muscle resistance and tissue to insulin, the decrement of insulin produced in the pancreas, and glucose absorption in the liver. Giving metformin to type 2 diabetes mellitus subjects increased glucose absorption in periphery tissue and liver but it did not impact insulin because metformin worked similarly to insulin and it did not impact beta cell function, so after or before metformin given, insulin concentration would not change, the effect of decrement of glucose following the concept of decay.